The Prediction of Fire Disaster Using BIM-Based Visualization for Expediting the Management Process - Kim, Dahee; Cha, Hee Sung; Jiang, Shaohua (Sustainability (Switzerland), 2023)
As buildings become larger and more complex, fire disaster management is of great concern. A building’s fire response and/or rescue system plays a pivotal role in minimizing fire victims and loss. To improve the current fire disaster management, it is important to link building (static) information, i.e., structural elements, fire escapes, and openings, with the fire (dynamic) information. When a building fire occurs, real-time fire information is required to be effectively linked with the on-site building information because the fire rescue teams, in most cases, are unfamiliar with the buildings. This study has proposed a Building Information Model (BIM)-based fire disaster management process which can digitally track the building data and the dynamic fire data simultaneously. To expedite this algorithm, an application program, i.e., Smart Fire Rescue Management (SFRM) has been developed using Revit™ software. A real-case project has been applied to evaluate the feasibility of the system. An expert survey has also been conducted to analyze the practical applicability. As a result, the system has been evaluated as exceptional, but it is necessary to upgrade the application from the practitioner’s viewpoint. The SFRM contributes to expediting the conventional disaster management process by enhancing the efficiency of the building fire response and/or rescue system.
Keywords: application programming interface; building information model; fire disaster control; smart disaster management; visualization